Identitas Budaya dan Komunikasi Lintas Budaya Antara Orang Tionghoa Totok Dengan Peranakan di Kota Padang - D, Delpa; Asmul, Ali (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the dynamics of cross-cultural communication between Chinese Totok de Peranakan in Padang city. Although both communities are descended from a common ancestor of Chinese origin. However both these ethnic groups have different cultural identities and traditions which indirectly these differences have led to the emergence of social distance between them. The study methodology is divided into three parts. Firstly, the data collection methodology employed interview guidelines (In-depth interviews) against the study informants. Second, the informant selection methodology uses the Snowball rule where the first informant is as the key informant. The informants consisted of seven people where 3 informants came from the Chinese community of Totok, 3 people came from the Chinese community of Peranakan and 1 informant came from the local residents of Padang city. Third, the data analysis methodology employed qualitative rules. The findings of the study revealed that the differences in cultural identity and traditions by each community caused them to live in isolation where the Chinese people have undergone a thorough process of assimilation so that the ethnic Chinese community speaks Minang fluently when communicating with ethnic Minangs cross-culturally. Manakala Chinese people still hold on to Chinese cultural values so they tend to speak Minang mixed with Mandarin dialect when communicating cross-culturally with Peranakan Chinese or communicating with locals.